2007
DOI: 10.1124/jpet.107.129650
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Sulfotransferase Enzymes by Prototypical Microsomal Enzyme Inducers in Mice

Abstract: In the present study, the regulation of the mRNA of 11 sulfotransferases (Sults) and two 3Ј-phosphoadenosine 5Ј-phosphosulfate synthase (PAPSs) isozymes by 15 microsomal enzyme inducers (MEI) in livers of male mice and five MEIs in livers of female mice was examined. These MEIs represent the transcriptionally mediated pathways: aryl hydrocarbon receptor (AhR), pregnane X receptor (PXR

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 56 publications
(78 reference statements)
5
77
0
Order By: Relevance
“…However, prototypical agonists for CAR, PPAR, PXR, or FXR did not influence SULT1C2 mRNA levels. These findings are consistent with those of Alnouti and Klaassen (2008) who reported that activators of CAR, PPAR, and PXR had no significant effect on SULT1C2 expression in the livers of male mice, and further suggest that there are some species differences in the regulation of SULT1C2 by nuclear receptors (Rondini et al, 2014).…”
Section: Discussionsupporting
confidence: 82%
“…However, prototypical agonists for CAR, PPAR, PXR, or FXR did not influence SULT1C2 mRNA levels. These findings are consistent with those of Alnouti and Klaassen (2008) who reported that activators of CAR, PPAR, and PXR had no significant effect on SULT1C2 expression in the livers of male mice, and further suggest that there are some species differences in the regulation of SULT1C2 by nuclear receptors (Rondini et al, 2014).…”
Section: Discussionsupporting
confidence: 82%
“…For example, in germ-free rats, the percentage of BA sulfates was about 10-fold higher in female than male fecal contents ( 23 ). The female-predominant sulfation of LCA is likely due to Sult2a, which is predominantly expressed in female mouse livers but is essentially absent from male mouse livers ( 24 ). Unlike sulfation of LCA, sulfations of CA and CDCA are malepredominant in mouse liver.…”
Section: Sulfation Of Ca and Cdca In Livers Of Mice Fed Basmentioning
confidence: 99%
“…Phase II metabolism or conjugation reactions consist of the glutathione S-transferases (Gsts), UDP glucuronosyltransferases (Ugts), and sulfotransferases (Sults) that usually function as detoxification enzymes in the liver (Jancova et al, 2010). The previously noted xenobiotic-and lipid-sensing transcription factors also regulate the expression of other non-P450 phase I enzymes as well as phase II enzymes in the liver (Alnouti and Klaassen, 2008;Knight et al, 2008;Buckley and Klaassen, 2009;Pratt-Hyatt et al, 2013). The GF mouse is an important model that allows mechanistic investigations of the role of intestinal microbiota in host drug metabolism.…”
Section: Introductionmentioning
confidence: 99%